Enhancing Employee Performance: The Impact of Transformational Leadership, Motivation, and Workload: Menyempurnakan Kinerja Karyawan: Dampak Kepemimpinan Transformasional, Motivasi, dan Beban Kerja.
This study investigates the influence of Transformational Leadership, Motivation, and Workload on employee performance in a sample of 55 respondents from the UD. Sinar Mas organization. Employing a non-probability sampling method with saturated sampling technique, the study utilizes multiple linear regression analysis to analyze the data. The findings demonstrate that Transformational Leadership, Motivation, and Workload all exert a positive and statistically significant impact on employee performance. This research underscores the importance of these factors in enhancing employee performance and provides valuable insights for organizations seeking to optimize their workforce’s productivity. Highlight: <div class="group w-full text-token-text-primary border-b border-black/10 gizmo:border-0 dark:border-gray-900/50 gizmo:dark:border-0 bg-gray-50 gizmo:bg-transparent dark:bg-[#444654] gizmo:dark:bg-transparent" data-testid="conversation-turn-5"> <div class="flex flex-1 gap-4 text-base mx-auto md:gap-6 gizmo:gap-3 md:max-w-2xl lg:max-w-[38rem] xl:max-w-3xl